How Digital Marketing and Brand Awareness Drive Online Purchasing: The Impact of Price Perception and Product Quality in Jakarta - Resti Pratama; Rini Hidayati (Research of Business and Management, 2026)
This study examines the influence of digital marketing, product quality, brand awareness, and price perception on online purchasing decisions for Kanky shoes. The population comprised consumers of Kanky shoes in Jakarta, excluding the Seribu Islands. The sample included respondents who had purchased and used Kanky shoes, actively used social media, were at least 17 years old, and resided in Jakarta (excluding the Seribu Islands). A quantitative research method was employed, with data collected through questionnaires using purposive sampling. Data were analyzed using SPSS and Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that digital marketing, brand awareness, and price perception have positive and significant effects on purchasing decisions. In contrast, product quality does not significantly influence purchasing decisions. Managerially, the results suggest that companies should maximize digital platforms to deliver targeted messages and strengthen brand awareness among broader audiences. Although product quality was not a significant predictor, maintaining high quality remains essential for building consumer trust and meeting market expectations through continuous innovation.